2005
DOI: 10.1021/ma0476689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mass Spectrometry Studies of an Amphiphilic Polyether-Based Rotaxane That Lacks an Enthalpic Driving Force for Threading

Abstract: A pure amphiphilic macrocrown ether (MC-12) was obtained by removing linear oligomers and larger macrocycles at the macrocyclization step, before proceeding with an established synthetic procedure. This pure MC-12 was used to synthesize a rotaxane composed of one MC-12 ring threaded with one end-capped poly(tetrahydrofuran) (PTHF) oligomer by equilibrating half an equivalent of the thread with an organized solution of MC-12 and end-capping the threads with excess 2-p-[tris(p-tertbutylphenyl)methyl]phenoxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In these cases, tandem mass spectrometry (MS/MS) can be utilized to determine how a polymer's constituents are connected to each other. MS/MS has been successfully used to characterize individual end groups of polymers Jackson, Green, & Bateman, 2006b;Jackson & Robertson, 2008;Polce et al, 2008a,b), differentiate isobaric or isomeric macromolecules (Wollyung et al, 2004), and identify macromolecular sequences and architectures (Arnould et al, 2002;Adamus et al, 2004;Wollyung et al, 2005;Wesdemiotis et al, 2006;Chaicharoen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, tandem mass spectrometry (MS/MS) can be utilized to determine how a polymer's constituents are connected to each other. MS/MS has been successfully used to characterize individual end groups of polymers Jackson, Green, & Bateman, 2006b;Jackson & Robertson, 2008;Polce et al, 2008a,b), differentiate isobaric or isomeric macromolecules (Wollyung et al, 2004), and identify macromolecular sequences and architectures (Arnould et al, 2002;Adamus et al, 2004;Wollyung et al, 2005;Wesdemiotis et al, 2006;Chaicharoen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, according to our samples, HABA-TMG 2 , afforded detection of poly [5]-to poly [14]rotaxanes, addressing a highest mass detected of about 20869 Da in positive mode ( Figure 5A and Table S2). Likewise, negative mode analysis led to the successful determination of poly [5]-to poly [17]rotaxanes with masses reaching 24804 Da ( Figure 5B and Table S2). …”
Section: Use Of Ionic Liquid Matricesmentioning
confidence: 97%
“…These residual CDs were probably coeluted with the PR-γCD-PDMS as described elsewhere for other guests with PRs. 17 Identification of free modified CDs showed a snapshot of the structure of CDs used during the PRs synthesis. Indeed, in positive ionization mode γCDs were mainly detected under sodiated forms at m/z 1319.41, m/z 1421.35 and in minor occurrence at m/z 1523.23 and m/z 1625.13 corresponding to the unmodified, monosulfated, disulfated and trisulfated forms, respectively ( Figure 2A).…”
Section: Preparation Of the Crystalline And Ionic Liquid Matricesmentioning
confidence: 99%
“…Additionally, nonpolar and aprotic solvents can be used with MALDI-TOF-MS, which offers the advantage of being able to detect high-MW structures, such as PR. A number of studies have demonstrated analysis of PR using MALDI-TOF-MS to obtain the molecular distribution of PR, in which the numbers of repeating units of linear polymers and threaded cyclic molecules were estimated. ,, Moreover, quantitative agreement with MALDI-TOF-MS and HPLC analysis was demonstrated in studies of an amphiphilic polyether-based rotaxane . Significantly, this end-capped rotaxane ionized in MALDI did not fragment in postsource decay, even though there was a low efficiency of the ionization, suggesting that a supramolecular structure of the rotaxane is stable in the ionization process of MALDI.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization (MALDI) and electrospray ionization (ESI) mass spectrometry (MS) are promising methods for analysis of PR with respect to low sample consumption and high throughput. ,,, A number of successful MS studies of PR have been reported. ESI using a high resolution mass spectrometer was previously employed to analyze CD-PR grafted with sulfo groups up to molecular weights (MWs) of several thousand kDa. , The number of PEG units, the threaded ratio, and the number of sulfo groups were all successfully elucidated using precise mass measurements.…”
Section: Introductionmentioning
confidence: 99%